FIT programme - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The Farm Implement and Tools (FIT) programme is a collaborative technical assistance programme between the International Labour Organization (ILO) and TOOL, a Dutch NGO. The FIT programme focuses on the upgrading of both the manufacturing and the...